MODELING THE KINETICS OF SILICA NANOCOLLOID FORMATION AND PRECIPITATION IN GEOLOGICALLY RELEVANT AQUEOUS SOLUTIONS - Conrad C.F.; Bandstra J.Z.; Brantley S.L.; Heaney P.J.; Icopini G.A.; Yasuhara H. (My University, 2007)
The kinetics of the formation and precipitation of nanocolloidal silica from geologically relevant aqueous solutions is investigated. Changes in monomeric (SiO2(mono)), nanocolloidal (SiO2(nano)) and precipitated silica (SiO2(ppt)) concentrations in aqueous solutions from pH 3 to 7, ionic strengths (IS) of 0.01 and 0.24 molal, and initial SiO2 concentrations of 20.8, 12.5 and 4.2 mmolal (reported in [Icopini, G.A., Brantley, S.L., Heaney, P.J., 2005. Kinetics of silica oligomerization and nanocolloid formation as a function of pH and ionic strength at 25 °C. Geochim. Cosmochim. Acta 69(2), 293-303.]) were fit using two kinetic models. The first model, termed the concentration model, is taken from Icopini et al. (2005) and assumes that the rate of change of SiO2(mono) as a function of time has a fourth-order dependence on the concentration of SiO2(mono) in solution. The second model, termed the supersaturation model, incorporates the equilibrium concentration of amorphous silica and predicts that polymerization will be a function of the degree of silica supersaturation in solution with respect to amorphous silica. While both models generally predicted similar rate constants for a given set of experimental conditions, the supersaturation model described the long-term equilibrium behavior of the SiO2(mono) fraction more accurately, resulting in significantly better fits of the monomeric data. No difference was seen between the model fits of the nanocolloidal silica fraction. At lower pH values (3-4), a metastable equilibrium was observed between SiO2(mono) and SiO2(nano). This equilibrium SiO2(mono) concentration was found to be 6 mmolal, or three times the reported solubility of bulk amorphous silica under the experimental conditions studied and corresponds to the predicted solubility of amorphous silica colloids approximately 3 nm in diameter. Atomic force microscopy was used to determine the average size of the primary nanocolloidal particles to be ~3 nm, which is in direct agreement with the solubility calculations. Larger aggregates of the primary nanocolloids were also observed to range in size from 30 to 40 nm. This work provides the first kinetic models describing the formation and evolution of nanocolloidal silica in environmentally relevant aqueous solutions. Results indicate that nanocolloidal silica is an important species at low pH and neutral pH at low ionic strengths and may play a more important role in geochemical cycles in natural aqueous systems than previously considered. © 2006 Elsevier Inc. All rights reserved.